Remény és félelem - Szanyi , Norbert (Kultúratudományi Szemle, 2022)
Hope and fear Norbert Szanyi According to Joachim Piegsa hope and fear are connected strongly to one another. Through them we can strengthen or even lose our courage for life. Hope is the way we relate to our future: through hope we envision a future, where our desires become real. Hope helps us to cope with the difficulties of life.